Breastfeeding Father berperan dalam Pemberian MP-ASI pada Bayi Usia 5-6 Bulan di Wilayah Puskesmas Lawang - Farida Farida; Sugijati Sugijati; Ari Kusmiwiyati (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Introducing complementary foods too early can potentially pose risks to the health of infants. Preventing early introduction of complementary foods requires family support, especially from the infant's husband/father. The father's role is to provide spiritual, moral, emotional, and physical support to the mother. The support of husbands through breastfeeding fathers is an important aspect that contributes to the success of mothers in providing exclusive breastfeeding so that early complementary feeding is not necessary. This study aims to determine the relationship between the implementation of the role of husbands through breastfeeding fathers and complementary feeding in infants aged 5-6 months in the working area of the Lawang Community Health Center in Malang Regency. This study used a cross-sectional analytical correlation design, with a population of 116 husbands of mothers breastfeeding infants aged 5-6 months. Sampling was conducted using purposive sampling, with a total of 33 people meeting the inclusion criteria. The instrument used was a questionnaire, and the data were analyzed using the Spearman Rank test. The analysis results showed a calculated r value of -0.540 with a p-value (sig) of 0.001, which is less than 0.05. These findings indicate that the husband's role has a significant influence on complementary feeding in the working area of the Lawang Community Health Center in Malang Regency. The implications of this study are very important as evaluation material for the community to implement breastfeeding fathers. Further research is recommended to analyze tricks that enable breastfeeding fathers to be easily implemented by every father.